2015
DOI: 10.1137/140985779
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Hybrid Systems by Feedback Control Based on Discrete-Time State Observations

Abstract: Recently, Mao [19] initiates the study the mean-square exponential stabilization of continuous-time hybrid stochastic differential equations by feedback controls based on discrete-time state observations. Mao [19] also obtains an upper bound on the duration τ between two consecutive state observations. However, it is due to the general technique used there that the bound on τ is not very sharp. In this paper, we will be able to establish a better bound on τ making use of Lyapunov functionals. We will not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 27 publications
0
122
0
Order By: Relevance
“…Due to the general techniques used in proofs in [16], the τ was required to be quite small in that paper. Mao and his group, therefore, modified the techniques and released the restriction on τ in [26,27]. We further observe that various effects, such as data transmission, may be time consuming.…”
Section: D(x(t)) = (F (X(t) R(t) T) + U(x(t) R(t) T))dt + G(x(t)mentioning
confidence: 92%
See 1 more Smart Citation
“…Due to the general techniques used in proofs in [16], the τ was required to be quite small in that paper. Mao and his group, therefore, modified the techniques and released the restriction on τ in [26,27]. We further observe that various effects, such as data transmission, may be time consuming.…”
Section: D(x(t)) = (F (X(t) R(t) T) + U(x(t) R(t) T))dt + G(x(t)mentioning
confidence: 92%
“…There are some available computer software, such as Matlab, for step 2, and the ideas for step 1 have been discussed in [26]. So we omit it here.…”
Section: Simumentioning
confidence: 99%
“…However, this is possible in our case and we will show this under the same conditions of Theorem 5.1 without any additional condition, unlike Theorem 5.2 which needs the additional condition (5.3). We should also point out that You et al [28] showed lim t\rightar\infty | x(t)| = 0 a.s. from E \int \infty 0 | x(t)| 2 dt < \infty (please note it is 2 but not q) under the linear growth condition. Our new proof given below not only overcomes the difficulty without the linear growth condition but is also much simplified.…”
Section: R(t))db(t)mentioning
confidence: 84%
“…On the other hand, You et al [28] showed this is possible if both coefficients f and g of the SDDE (4.1) satisfy the linear growth condition. However, we are interested in the SDDEs which do not satisfy the linear growth condition in this paper.…”
Section: R(t))db(t)mentioning
confidence: 99%
“…However, due to the existence of zero‐order holder, the sampled‐data controller holding the control signal constant during the sampling period introduces discontinuity to the systems that complicates dynamic behaviors of systems and makes the analysis and control design more difficult. In recent years, sampled‐data control has been received increasing attentions in the control field . In the literature, there are three main approaches for sampled‐data control design for nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%